Method for preparing self-healing microcapsules for asphalt and quantitatively evaluating healing performance of self-healing microcapsules

By adding prepared self-healing microcapsules to asphalt, the problems of complex preparation process and poor performance in the prior art are solved, and the efficient self-healing function of asphalt pavement is realized, and the self-healing is accurately characterized by quantitative evaluation methods Performance, providing scientific basis for material design, extending the service life of the road surface.

CN119463220AInactive Publication Date: 2025-02-18HUAZHONG UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411771619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has unreacted monomers or impurities residues when preparing asphalt pavement self-healing microcapsules, which affects the performance of the polymer and the production process is complex, increasing production costs and environmental pollution risks. At the same time, the existing microcapsule self-healing performance evaluation methods rely on empirical indicators, making it difficult to accurately quantify the healing ability, limiting the optimization of material design and determination of optimal dosage.

Method used

Self-healing microcapsules were prepared by vacuum pretreatment and encapsulation treatment using fly ash float beads, healing agents and aqueous polyvinyl alcohol solution as raw materials, and were added to the asphalt to prepare modified asphalt. The self-healing performance was quantified by physical indicators such as fatigue factor recovery rate using linear amplitude scanning test, fatigue test and healing test.

Benefits of technology

The prepared self-healing microcapsules have smooth surfaces, complete capsule wall structure, high chemical stability and thermal stability, which significantly improves the self-healing function of asphalt pavement. Quantitative evaluation methods can accurately characterize the dynamic evolution process of asphalt self-healing, provide scientific basis for material design, extend the service life of the road surface, and reduce maintenance and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463220A_ABST
    Figure CN119463220A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road engineering, in particular to a self-healing microcapsule preparation and healing performance quantitative evaluation method for asphalt, which comprises the following steps: immersing pretreated fly ash floating beads in waste oil, carrying out vacuum adsorption until saturation, taking out, wiping, spraying a polyvinyl alcohol aqueous solution for packaging, and finally mixing with matrix asphalt to obtain modified asphalt. The prepared self-healing microcapsule is smooth in surface, complete in capsule wall structure, high in chemical stability and good in thermal stability; the self-healing microcapsule modified asphalt is prepared after the self-healing microcapsule is added into the matrix asphalt, when microcracks are generated in the modified asphalt, the capsule wall is broken, the healing agent is released to achieve the purpose of repairing the microcracks, and the self-healing function is outstanding; the physical significance of evaluating the asphalt self-healing performance by adopting the fatigue factor recovery rate is clear, and the dynamic evolution process of asphalt self-healing can be effectively represented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering, and in particular to a method for preparing self-healing microcapsules for asphalt and quantitatively evaluating the healing performance. Background Art

[0002] Due to adverse factors such as harsh environment, heavy load and overload, improper construction management, etc., early road diseases occur frequently, which brings great challenges to road operation and maintenance. As one of the typical early diseases of asphalt pavement, the process of pavement cracks from initiation to complete failure of the pavement is a dynamic evolution process. The faster the cracks develop, the shorter the service life of the pavement. For the tiny cracks formed in the early stage of asphalt pavement, if reasonable means are not taken to repair them in time, it is very easy to cause secondary pavement diseases, including potholes, looseness, rutting, etc. Therefore, how to repair crack-type diseases of asphalt pavement in a timely and efficient manner has become a focus of widespread concern in the road engineering community. With the development of multifunctionality and intelligent materials, traditional maintenance methods no longer meet the needs of high-quality development of asphalt pavements. In contrast, self-healing asphalt pavements can repair cracked parts of asphalt pavements in a timely and efficient manner, and are currently receiving widespread attention.

[0003] Self-healing microcapsules are a type of self-healing smart material that uses microparticle encapsulation technology to integrate microcapsules containing healing substances into the material, giving it the ability to repair defects or damaged areas. If this material is used in the road field, it can effectively extend the service life of the road surface and reduce maintenance and repair costs. Under the microcapsule-type self-healing asphalt pavement system, certain requirements are placed on the mechanical properties of self-healing microcapsule materials. First, during the normal use of asphalt pavement, self-healing microcapsules should be able to withstand the repeated effects of vehicle loads, especially under heavy loads, and should not break prematurely; secondly, when microcracks occur in the asphalt pavement, the self-healing microcapsules should break in time and release the healing agent to prevent the cracks from expanding. The preparation process of self-healing microcapsules and their accurate quantitative evaluation of the healing performance of asphalt materials are crucial to optimizing the design of self-healing materials and improving the fatigue life of asphalt materials.

[0004] In terms of the preparation technology of asphalt self-healing microcapsules, patent CN112029303A discloses a microcapsule modified asphalt and its preparation method, and patent CN104744729A discloses a preparation method for microcapsules using in-situ polymerization. However, the existing preparation methods have some common disadvantages. First, due to the influence of various factors such as reaction conditions, monomer concentration, solvent properties, etc., some unreacted monomers or impurities may remain in the product. These residues may affect the properties of the polymer, such as purity and stability. Secondly, whether it is in-situ polymerization or interfacial polymerization, specific reaction conditions are required, such as temperature, pH value, type and concentration of catalyst, etc. The precise control of these conditions is crucial to ensure the smooth progress of the polymerization reaction and obtain high-quality polymers. However, in actual operation, the control of these conditions may be difficult, which increases the production cost and process complexity. Finally, after the polymerization reaction is completed, subsequent treatment is usually required to remove unreacted monomers, catalyst residues, and solvents. These subsequent treatment steps may be cumbersome, requiring additional equipment and time investment, thereby increasing production costs. At the same time, improper treatment may also lead to environmental pollution and safety issues. Therefore, although self-healing microcapsules for asphalt pavements can be prepared at present, the above disadvantages limit the widespread application of self-healing microcapsules in asphalt pavements.

[0005] In terms of quantitative evaluation of the healing performance of self-healing microcapsules, CN201711420560.2 discloses a numerical simulation method for the damage and healing mechanism of microcapsule self-healing materials, and uses a fluid-solid coupling numerical method to simulate the damage initiation and expansion process of microcapsule self-healing materials under load, revealing the damage and healing process of microcapsule self-healing materials. Patent CN202111619262.2 discloses a test and evaluation method for the self-healing property of graphene microcapsule asphalt mortar under dual mechanism action. This method determines the linear viscoelastic range of graphene microcapsule asphalt mortar based on stress scanning test and determines the fatigue test control load. Then a fatigue test is carried out to analyze the change law of the dynamic modulus of graphene microcapsule asphalt mortar with the number of load actions. The current patents on the evaluation method of microcapsule self-healing performance focus on the use of a series of diversified technical means for comprehensive analysis, including but not limited to numerical simulation, microscopy, permeability testing, compressive strength gain rate calculation, and microstructure and chemical composition methods, so as to comprehensively measure the self-healing efficiency of microcapsules. However, these existing patents still face certain limitations in the field of microcapsule self-healing performance evaluation, especially when relying on empirical indicators for evaluation. Such indicators are usually difficult to accurately quantify the healing ability of microcapsules, which in turn limits their effectiveness and practicality in guiding the design optimization of microcapsule materials and determining the optimal dosage. Summary of the invention

[0006] In order to address the deficiencies in the prior art, the present invention provides a method for preparing self-healing microcapsules for asphalt and quantitatively evaluating the healing performance. The self-healing microcapsules are added to asphalt, and the resulting modified asphalt has outstanding self-healing function.

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing self-healing microcapsules for asphalt, comprising the following steps:

[0008] (1) Weigh the following raw materials: fly ash floating beads, healing agent and polyvinyl alcohol aqueous solution;

[0009] (2) drying the fly ash floating beads to constant weight, and placing them in a closed drying oven after the surface temperature thereof cools to below 30° C., and performing vacuum pretreatment for 40 min under a negative pressure of 0.1 MPa to obtain pretreated fly ash floating beads;

[0010] (3) Put the pretreated fly ash beads into a 200-mesh mesh bag and immerse it in a container containing a healing agent;

[0011] (4) The vessel is transferred to a vacuum drying oven, vacuumed, and allowed to stand for 20 minutes at a negative pressure of 0.1 MPa to allow the pretreated fly ash floating beads to reach a saturated state; then, the vessel is taken out from the healing agent, and the surface liquid is wiped off to reach a surface dry state, thereby obtaining fly ash floating beads containing the healing agent;

[0012] (5) Spraying the polyvinyl alcohol aqueous solution on the surface of the fly ash floating beads containing the healing agent for packaging treatment, and drying at room temperature for 24 hours to obtain self-healing microcapsules.

[0013] Preferably, in step (1), the raw materials are composed of 45-55% fly ash floating beads, 40-50% healing agent and 3-7% polyvinyl alcohol aqueous solution in terms of mass percentage.

[0014] Preferably, the fly ash floating beads are 80-120 meshes.

[0015] Preferably, in the polyvinyl alcohol aqueous solution, the polyvinyl alcohol accounts for 7-9% of the water mass.

[0016] Preferably, in step (1), the healing agent is one or more of waste engine oil, plant waste oil, and epoxidized soybean oil.

[0017] The present invention provides a method for preparing modified asphalt using self-healing microcapsules for asphalt, comprising the following steps:

[0018] S11, placing the base asphalt in a high-speed shearing machine, heating it to 130-150°C, and then raising the temperature to 155-175°C;

[0019] S12, adjusting the speed of the high-speed shearing machine to 1200-1500 rpm, and then pouring the self-healing microcapsules at a uniform speed. When the self-healing microcapsules are completely added, adjusting the speed to 1800-2200 rpm, maintaining shear stirring for 15-25 minutes, and obtaining a stirred material;

[0020] S13. Place the stirred material in an oven at 80° C. to swell and develop for 30 minutes to obtain modified asphalt with self-healing function.

[0021] In step S11, the base asphalt is any one of 70# base asphalt, 90# base asphalt, and SBS modified asphalt.

[0022] In steps S11 to S12, the mass ratio of the matrix asphalt to the self-healing microcapsules is 100:3.

[0023] The present invention also provides a method for quantitatively evaluating the healing performance of modified asphalt, comprising the following steps:

[0024] S21, linear amplitude sweep test

[0025] The modified asphalt was kept at a constant temperature at the test temperature, and a gradually increasing sinusoidal load was applied to the modified asphalt through a dynamic shear rheometer. Its complex shear modulus was recorded, and the corresponding point where the complex shear modulus dropped to 90% of the initial value was determined. The strain amplitude at this point was the linear viscoelastic limit strain threshold ε of the modified asphalt. t ;

[0026] S22. Fatigue test Ⅰ

[0027] The modified asphalt was subjected to strain time scanning test using a dynamic shear rheometer at a test temperature of 25 °C and a strain level of ε t , the loading frequency is 10Hz; the time-fatigue factor test graph is obtained with the test time as the horizontal and vertical scales and the fatigue factor |G*sinδ| as the vertical coordinate; when the fatigue factor of the modified asphalt is reduced to 50% of the initial fatigue factor, the fatigue test I ends; the initial fatigue factor F0 of the modified asphalt and the termination fatigue factor F at the end of the test are recorded b ;

[0028] S23. Healing test 1

[0029] After the fatigue test I is completed, the test temperature is controlled, the load is removed to allow the modified asphalt to enter the healing period, and the healing time t is set. When the healing time t is reached, the healing test I is terminated;

[0030] S24, fatigue test II

[0031] After completing the healing test Ι, the strain time sweep test was continued, and the strain level was selected as ε tThe loading frequency is 10 Hz. The termination condition of fatigue test II is set to when the fatigue factor is reduced to 20% of the initial fatigue factor F0. The initial fatigue factor F after healing is recorded. a , and the fatigue factor before and after healing has the same value F' a , the value of the end fatigue factor after healing is the same as that before healing F' b , t1 is the F after the interval a Descending to F' b Loading time; t2 is the F' before the interval a Down to F b Loading time;

[0032] S25. The self-healing performance of modified asphalt is calculated as follows:

[0033]

[0034] Among them, the fatigue factor recovery rate FI is used to characterize the self-healing effect.

[0035] The present invention provides a method for preparing self-healing microcapsules for asphalt and quantitatively evaluating the healing performance, which has the following beneficial effects compared with the prior art:

[0036] The self-healing microcapsules prepared by the present invention have a smooth surface, a complete capsule wall structure and high chemical stability, and also have good thermal stability; the self-healing microcapsules are added to the matrix asphalt to prepare the self-healing microcapsule modified asphalt, and when microcracks are generated inside the modified asphalt, the capsule wall ruptures, and the healing agent is released to achieve the purpose of repairing the microcracks, and the self-healing function is outstanding; the fatigue factor recovery rate is used to evaluate the self-healing performance of asphalt, which has a clear physical meaning, can effectively characterize the dynamic evolution process of asphalt self-healing, can accurately quantify its healing effect, and can provide a scientific basis for the design of asphalt self-healing materials, thereby ensuring the service life of asphalt pavement and reducing the cost of pavement maintenance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0038] Figure 1 Environmental scanning electron microscope images of the microscopic morphology of the self-healing microcapsules before and after encapsulation of the present invention;

[0039] Figure 2 This is a thermogravimetric analysis diagram of the self-healing microcapsule of the present invention;

[0040] Figure 3 This is a comparison chart of the liquid absorption rate results of fly ash floating beads with different particle sizes of the present invention;

[0041] Figure 4 It is a fatigue factor variation curve of asphalt before and after healing in the DSR fatigue-healing test of the present invention;

[0042] Figure 5 This is a comparison chart of the DSR fatigue-healing test results of different asphalt samples of the present invention. DETAILED DESCRIPTION

[0043] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.

[0044] Example 1

[0045] A method for preparing self-healing microcapsules for asphalt, comprising:

[0046] The fly ash beads (80-120 mesh) sample was placed in a 60°C oven and dried to constant weight, then the sample was taken out of the drying oven and the surface temperature was cooled to below 30°C, and the sample was placed in a closed vacuum drying oven and pretreated for 40 minutes under a negative pressure of 0.1 MPa; the pretreated sample was placed in a 200-mesh mesh bag, and then immersed in a vessel filled with epoxy soybean oil ESO; the vessel was transferred to a vacuum drying oven, the vacuum state was drawn, and it was left to stand for 20 minutes under a negative pressure of 0.1 MPa until the fly ash beads reached a saturated state; when the fly ash beads were saturated, the sample was taken out of the solution, and the surface liquid was wiped with a wet rag to make it dry. Then, a high-pressure spray bottle was used to spray the polyvinyl alcohol aqueous solution on the surface of the sample for encapsulation treatment, and it was dried at room temperature for 24 hours to obtain the desired self-healing microcapsules for asphalt.

[0047] In terms of mass percentage, the raw materials are composed of 50% fly ash floating beads, 45% epoxy soybean oil and 5% polyvinyl alcohol aqueous solution, wherein the polyvinyl alcohol accounts for 8% of the water mass.

[0048] The appearance of the self-healing microcapsules was observed by environmental scanning electron microscopy. Figure 1 (a)

[0049] The thermal stability of the self-healing microcapsules was tested using a comprehensive thermogravimetric analyzer to meet the requirements of asphalt pavement construction. The initial temperature was set at 50 °C, a stepwise isothermal process with a scan rate of 10 °C / min, and a N2 flow rate of 20 ml / min to more accurately capture the mass change. The test results are shown in Figure 2. Figure 2 As shown, when the temperature rises to 180 °C, the mass of the microcapsules loses about 10%.

[0050] Example 2

[0051] A method for preparing self-healing microcapsules for asphalt, comprising:

[0052] The fly ash floating beads (80-120 mesh) sample was placed in a 60°C oven and dried to constant weight, then the sample was taken out of the drying oven and the surface temperature was cooled to below 30°C, and the sample was placed in a closed vacuum drying oven and pretreated for 40 minutes under a negative pressure of 0.1MPa; the pretreated sample was placed in a 200-mesh mesh bag, and then immersed in a vessel filled with vegetable waste oil; the vessel was transferred to a vacuum drying oven, the vacuum state was drawn, and it was left to stand for 20 minutes under a negative pressure of 0.1MPa until the fly ash floating beads reached a saturated state; when the fly ash floating beads were saturated, the sample was taken out of the solution, and the surface liquid was wiped with a wet rag to make it dry. Then, a high-pressure spray bottle was used to spray the polyvinyl alcohol aqueous solution on the surface of the sample for encapsulation treatment, and it was dried at room temperature for 24 hours to obtain the desired self-healing microcapsules for asphalt.

[0053] In terms of mass percentage, the raw materials are composed of 47% fly ash floating beads, 50% plant waste oil and 3% polyvinyl alcohol aqueous solution, wherein the polyvinyl alcohol accounts for 7% of the water mass.

[0054] Example 3

[0055] A method for preparing self-healing microcapsules for asphalt, comprising:

[0056] The fly ash floating beads (80-120 mesh) sample was placed in a 60℃ oven and dried to constant weight, then the sample was taken out of the drying oven and the surface temperature was cooled to below 30℃, and the sample was placed in a closed vacuum drying oven and pretreated for 40 minutes under a negative pressure of 0.1MPa; the pretreated sample was placed in a 200-mesh mesh bag, and then immersed in a vessel filled with waste engine oil; the vessel was transferred to a vacuum drying oven, vacuumed, and left to stand for 20 minutes under a negative pressure of 0.1MPa until the fly ash floating beads reached a saturated state; when the fly ash floating beads were saturated, the sample was taken out of the solution, and the surface liquid was wiped with a wet rag to make it dry. Then a high-pressure spray bottle was used to spray the polyvinyl alcohol aqueous solution on the surface of the sample for encapsulation treatment, and dried at room temperature for 24 hours to obtain the desired self-healing microcapsules for asphalt.

[0057] In terms of mass percentage, the raw materials are composed of 53% fly ash floating beads, 40% waste engine oil and 7% polyvinyl alcohol aqueous solution, in which the polyvinyl alcohol accounts for 9% of the water mass.

[0058] Example 4

[0059] A method for preparing modified asphalt using self-healing microcapsules for asphalt, comprising:

[0060] Put 200g of 70# matrix asphalt sample into a high-speed shearing machine, heat it to 140°C, and then increase the temperature to 160°C; adjust the speed of the high-speed shearing machine to 1500rpm, and then pour 6g of self-healing microcapsules (prepared in Example 1) into it at a uniform speed. When the self-healing microcapsules (prepared in Example 1) are completely added, adjust the speed to 2000rpm, and maintain shearing stirring for 20min; after the shearing is completed, put the obtained stirred material into an oven at 80°C for swelling and development for 30min to obtain modified asphalt with self-healing function.

[0061] Example 5

[0062] A method for preparing modified asphalt using self-healing microcapsules for asphalt, comprising:

[0063] Put 200g of 90# base asphalt sample into a high-speed shearing machine, heat it to 150°C, and then increase the temperature to 155°C; adjust the speed of the high-speed shearing machine to 1500rpm, and then pour 6g of self-healing microcapsules (prepared in Example 1) into it at a uniform speed. When the self-healing microcapsules (prepared in Example 1) are completely added, adjust the speed to 1800rpm, and maintain shear stirring for 25min; after the shearing is completed, put the obtained stirred material into an oven at 80°C for swelling and development for 30min to obtain modified asphalt with self-healing function.

[0064] Example 6

[0065] A method for preparing modified asphalt using self-healing microcapsules for asphalt, comprising:

[0066] Put 200g of SBS modified asphalt sample into a high-speed shearing machine, heat it to 130°C, and then increase the temperature to 175°C; adjust the speed of the high-speed shearing machine to 1200rpm, and then pour 6g of self-healing microcapsules (prepared in Example 1) into it at a uniform speed. When the self-healing microcapsules (prepared in Example 1) are completely added, adjust the speed to 2200rpm, and maintain shear stirring for 15min; after the shearing is completed, put the obtained stirred material into an oven at 80°C for swelling and development for 30min to obtain modified asphalt with self-healing function.

[0067] Example 7

[0068] A method for quantitatively evaluating the healing performance of modified asphalt, comprising:

[0069] S21, linear amplitude sweep test

[0070] The modified asphalt was kept at a constant temperature of 25°C. A gradually increasing sinusoidal load was applied to the modified asphalt through a dynamic shear rheometer. Its complex shear modulus was recorded and the corresponding point where the complex shear modulus dropped to 90% of the initial value was determined. The strain amplitude at this point was the linear viscoelastic limit strain threshold ε of the modified asphalt. t ;

[0071] S22. Fatigue test Ⅰ

[0072] The modified asphalt was subjected to strain time scanning test using a dynamic shear rheometer at a test temperature of 25 °C and a strain level of ε t (i.e., the linear viscoelastic limit strain threshold ε in step S21 t ), the loading frequency is 10Hz; the time-fatigue factor test graph is obtained with the test time as the horizontal and vertical scales and the fatigue factor |G*sinδ| as the vertical coordinate; when the fatigue factor of the modified asphalt is reduced to 50% of the initial fatigue factor, the fatigue test I ends; the initial fatigue factor F0 of the modified asphalt and the termination fatigue factor F at the end of the test are recorded b ;

[0073] S23. Healing test 1

[0074] After the fatigue test I is completed, the test temperature is controlled to 25°C, the load is removed to allow the modified asphalt to enter the healing period, and the healing time t is set. When the healing time t is reached, the healing test I is terminated;

[0075] S24, fatigue test II

[0076] After completing the healing test Ι, the strain time sweep test was continued, and the strain level was selected as ε t The loading frequency is 10 Hz. The termination condition of fatigue test II is set to when the fatigue factor is reduced to 20% of the initial fatigue factor F0. The initial fatigue factor F after healing is recorded. a , and the fatigue factor before and after healing has the same value F' a , the value of the end fatigue factor after healing is the same as that before healing F' b , t1 is the F after the interval a Descending to F' b Loading time; t2 is the F' before the interval a Down to F b Loading time;

[0077] S25. The self-healing performance of modified asphalt is calculated as follows:

[0078]

[0079] Among them, the fatigue factor recovery rate FI is used to characterize the self-healing effect.

[0080] In this embodiment, the modified asphalt used is the modified asphalt with self-healing function prepared in Example 4.

[0081] Comparative Example 1

[0082] Self-healing microcapsules were prepared according to the method in Example 1, except that after the adsorption process, no polyvinyl alcohol aqueous solution was used for encapsulation.

[0083] The external morphology of the self-healing microcapsules was observed using an environmental scanning electron microscope. Figure 1 (b)

[0084] At the same time, the thermal stability of the self-healing microcapsules was tested by a comprehensive thermogravimetric analyzer. Figure 2 shown.

[0085] Comparative Example 2

[0086] Self-healing microcapsules were prepared according to the method in Example 2. The difference from Example 1 is that fly ash floating beads with mesh sizes of 20-40, 40-80, 120-160, and 160-200 were used to compare the liquid absorption rates. The results are as follows: Figure 3 shown.

[0087] Comparative Example 3

[0088] According to the quantitative evaluation method in Example 7, the difference from Example 7 is that 70# matrix asphalt is selected to carry out DSR fatigue-healing test. Figure 5 shown.

[0089] Comparative Example 4

[0090] According to the method in Example 4, the difference from Example 4 is that 6g of self-healing microcapsules are reduced to 2g, and the resulting product is subjected to the DSR fatigue-healing test in Example 7. The results are as follows: Figure 5 shown.

[0091] Comparative Example 5

[0092] According to the method in Example 4, the difference from Example 4 is that the amount of self-healing microcapsules is increased from 6 g to 10 g, and the resulting product is subjected to the DSR fatigue-healing test in Example 7. The results are as follows: Figure 5 shown.

[0093] Test results and verification

[0094] 1. The evaluation method in Example 7 was used to perform DSR fatigue-healing test on the modified asphalt with self-healing function in Example 4 and the 70# base asphalt in Comparative Example 2; meanwhile, the test results were verified by ductility recovery test. The specific results are shown in Table 1-2.

[0095] Table 1DSR healing-recovery test results

[0096] Group <![CDATA[F0(Pa)]]> <![CDATA[F a (Well)]]> <![CDATA[F b (Well)]]> <![CDATA[t1(s)]]> <![CDATA[t2(s)]]> FI(%) Self-healing modified asphalt 2.62E+06 1.77E+06 1.30E+06 95 139 24.4 70# Base Asphalt 2.13E+06 1.39E+06 1.06E+06 73 156 14.2

[0097] Table 2 Ductility recovery test results

[0098] Group Initial elongation (cm) Elongation after fracture recovery (cm) Recovery rate (%) Self-healing modified asphalt 19.1 14.8 77.5 70# Base Asphalt 24.3 10.4 42.8

[0099] The recovery rate in the ductility recovery test is a key indicator, which reflects the ability of the material to recover to its original state after being subjected to external force. This recovery ability is positively correlated with the fatigue factor recovery rate of the material.

[0100] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing self-healing microcapsules for asphalt, characterized in that: The following steps are involved: (1) Weigh the following raw materials: fly ash floating beads, healing agent and polyvinyl alcohol aqueous solution; (2) drying the fly ash floating beads to constant weight, and placing them in a closed drying oven after the surface temperature thereof cools to below 30° C., and performing vacuum pretreatment for 40 min under a negative pressure of 0.1 MPa to obtain pretreated fly ash floating beads; (3) Put the pretreated fly ash beads into a 200-mesh mesh bag and immerse it in a container containing a healing agent; (4) The vessel is transferred to a vacuum drying oven, vacuumed, and allowed to stand for 20 minutes at a negative pressure of 0.1 MPa to allow the pretreated fly ash floating beads to reach a saturated state; then, the vessel is taken out from the healing agent, and the surface liquid is wiped off to reach a surface dry state, thereby obtaining fly ash floating beads containing the healing agent; (5) Spraying the polyvinyl alcohol aqueous solution on the surface of the fly ash floating beads containing the healing agent for packaging treatment, and drying at room temperature for 24 hours to obtain self-healing microcapsules.

2. The self-healing microcapsule for asphalt according to claim 1, characterized in that: In step (1), the raw materials are composed of 45-55% fly ash floating beads, 40-50% healing agent and 3-7% polyvinyl alcohol aqueous solution in terms of mass percentage.

3. The self-healing microcapsule for asphalt according to claim 2, characterized in that: The fly ash floating beads have a mesh size of 80 to 120.

4. The self-healing microcapsule for asphalt according to claim 2, characterized in that: In the polyvinyl alcohol aqueous solution, polyvinyl alcohol accounts for 7-9% of the mass of water.

5. The self-healing microcapsule for asphalt according to claim 1, characterized in that: In step (1), the healing agent is one or more of waste engine oil, plant waste oil, and epoxidized soybean oil.

6. A method for preparing modified asphalt using the self-healing microcapsules for asphalt as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S11, placing the base asphalt in a high-speed shearing machine, heating it to 130-150°C, and then raising the temperature to 155-175°C; S12, adjusting the speed of the high-speed shearing machine to 1200-1500 rpm, and then pouring the self-healing microcapsules at a uniform speed. When the self-healing microcapsules are completely added, adjusting the speed to 1800-2200 rpm, maintaining shear stirring for 15-25 minutes, and obtaining a stirred material; S13. Place the stirred material in an oven at 80° C. to swell and develop for 30 minutes to obtain modified asphalt with self-healing function.

7. The method for preparing modified asphalt using self-healing microcapsules for asphalt according to claim 6, characterized in that: In step S11, the base asphalt is any one of 70# base asphalt, 90# base asphalt, and SBS modified asphalt.

8. The method for preparing modified asphalt using self-healing microcapsules for asphalt according to claim 6, characterized in that: In steps S11 to S12, the mass ratio of the matrix asphalt to the self-healing microcapsules is 100:

3.

9. A method for quantitatively evaluating the healing performance of modified asphalt according to any one of claims 6 to 8, characterized in that: The following steps are involved: S21, linear amplitude sweep test The modified asphalt was kept at a constant temperature at the test temperature, and a gradually increasing sinusoidal load was applied to the modified asphalt through a dynamic shear rheometer. Its complex shear modulus was recorded, and the corresponding point where the complex shear modulus dropped to 90% of the initial value was determined. The strain amplitude at this point was the linear viscoelastic limit strain threshold ε of the modified asphalt. t ; S22. Fatigue test Ⅰ The modified asphalt was subjected to strain time scanning test using a dynamic shear rheometer at a test temperature of 25 °C and a strain level of ε t , the loading frequency is 10Hz; the time-fatigue factor test graph is obtained with the test time as the horizontal and vertical scales and the fatigue factor |G*sinδ| as the vertical coordinate; when the fatigue factor of the modified asphalt is reduced to 50% of the initial fatigue factor, the fatigue test I ends; the initial fatigue factor F0 of the modified asphalt and the termination fatigue factor F at the end of the test are recorded b ; S23. Healing test 1 After the fatigue test I is completed, the test temperature is controlled, the load is removed to allow the modified asphalt to enter the healing period, and the healing time t is set. When the healing time t is reached, the healing test I is terminated; S24, fatigue test II After completing the healing test Ι, the strain time sweep test was continued, and the strain level was selected as ε t The loading frequency is 10 Hz. The termination condition of fatigue test II is set to when the fatigue factor is reduced to 20% of the initial fatigue factor F0. The initial fatigue factor F after healing is recorded. a , and the fatigue factor before and after healing has the same value F' a , the value of the end fatigue factor after healing is the same as that before healing F' b , t1 is the F after the interval a Descending to F' b Loading time; t2 is the F' before the interval a Down to F b Loading time; S25. The self-healing performance of modified asphalt is calculated as follows: Among them, the fatigue factor recovery rate FI is used to characterize the self-healing effect.

Citation Information

Patent Citations

  • Microcapsule capable of enhancing self-healing capability of asphalt and preparation method of microcapsule

    CN104744729A

  • A numerical simulation method for damage and healing mechanism of microcapsule self-healing materials

    CN108038329B

  • Microcapsule modified asphalt and preparation method thereof

    CN112029303A

  • Evaluation Method for Self-Healing Properties of Graphene Microcapsule Asphalt Mortar under Dual-Mechanism Action

    CN114354403B